Systemic sarcoidosis mimicking metastatic renal cell carcinoma with subsequent cardiac involvement. (2021) - Frohlich, Michael; Buhlaiga, Najwa; Wang, Hangjun; Patenaude, Francois; Sirois, Christian; Sakr, Lama
Abstract: There exists a well-established association between sarcoidosis and many solid and hematologic malignancies however it is a less frequently described phenomenon in patients with renal cell carcinoma. Moreover the majority of described cases presented with local sarcoid-like reactions in close proximity to the tumor with comparatively few reports of more distant disease. Given the relatively low number of cases there remains a great deal of uncertainty surrounding the clinical behaviour of sarcoidosis in the setting of renal cell carcinoma. We report the case of a patient with surgically resected renal cell carcinoma who, several years later, developed bilateral pulmonary nodules, intra-thoracic lymphadenopathy as well as splenic, hepatic and osseous lesions. After extensive investigation, culminating in video-assisted thoracoscopic surgical resection, he was found to have sarcoidosis. He remained asymptomatic for many years before being diagnosed with cardiac sarcoidosis, which was found to be inactive and did not require any treatment. Both his sarcoidosis and underlying renal cell carcinoma have remained in remission to date. This case highlights the variable behaviour of sarcoidosis in these patients and underscores the importance of obtaining an accurate tissue diagnosis in the setting of suspected metastatic disease. Additionally, it underscores the importance of close monitoring and long-term follow up as these patients may develop significant organ involvement, even many years after diagnosis. Interestingly the patient's renal cell carcinoma remained in remission, raising questions about whether the development of sarcoidosis portends a better prognosis in patients with an underlying solid malignancy.